Strengthening the Epistemology of Religious Moderation Based on the Values of Unity of Science - Nor Hadi; Abdul Rohman; Ahmad Umam Aufi (Yayasan Darussalam Bengkulu, 2025)
This study aims to analyze the value of the unity of knowledge in the Qur’an as an epistemological foundation for strengthening religious moderation in the Islamic Religious Education learning at SD Muhammadiyah Plus Semarang, SD IT Cahaya, Bangsa, MI Miftakhul Akhlaqiyah dan MI Takhasus Darul Ulum Semarang, Indonesia, with a focus on the aspects of understanding, implementation, and challenges. This study employs a qualitative approach with a case study design, as it allows for an in-depth exploration of phenomena within a real-world learning context. Data were collected through in-depth interviews and participatory observation in the classroom, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the value of the unity of knowledge is understood as an epistemological-theological foundation that affirms that all knowledge originates from God, thereby fostering an inclusive attitude, rejecting claims of exclusive truth, and integrating normative and contextual approaches in understanding diversity. The application of these values takes three main forms: the integration of an interdisciplinary curriculum that links Islamic teachings with the social sciences and humanities; the implementation of dialogic-reflective learning that encourages open discussion and respect for differences; and experiential learning through field activities that reinforce the internalization of the values of moderation. However, this implementation still faces challenges in the form of a dichotomous scientific paradigm, limitations in teachers’ pedagogical competencies, and the influence of unfiltered digital information. Therefore, it is necessary to strengthen academic capacity, learning innovation, and critical digital literacy. This study contributes to strengthening an integrative Islamic education paradigm grounded in religious moderation.